Derivation of 6-hour unitgraphs for Barakar (D. V. C. ) and Yamuna catchments for flood forecasting - NARAYANAN, PANKAJA; HASIJA , S.C.; RAO, D. V. L. N. (MAUSAM, 1977)
In this paper, series of unit hydrographs were derived assuming a 6-hr unit period for the Burukur and Yumuna catchments. The best fit unit hydrograph is selected mainly by the least square’s method. Several important relationships to apply the method for operational use were also derived. These relationships are in the form of API initial loss relationships and the inter-relationship of rainfall intensity, loss rate and API. Although the results are based upon a small sample, it has been possible to derive the above relationships. At the end a correction diagram IS also given to enable the user to correct the time of occurrence as well as the magnitude of the flood peak.